PENATAAN LINGKUNGAN SEBAGAI INSTRUMEN PENCEGAHAN KEJAHATAN SEKSUAL TERHADAP ANAK STUDI KASUS KOTA BANDAR LAMPUNG - Asirin Asirin; Lianita Zanith (Universitas Gadjah Mada, 2017)
The incidence of sexual crimes against children occurs in many areas of Bandar Lampung Municipality. This study aims to explore the condition and the lack of environmental arrangement in Bandar Lampung Municipality, in order to build a safe environment that can prevent sexual crimes in children. The study limits the scope of the material using the mainframe conceptual framework of neighborhood planning (neighborhood planning) and interventions for safe environmen- tal arrangement for children’s lessons from Tokyo Municipality, Japan. This research uses qualitative methods of analysis and verification effort (reliability and validity). The results show that Bandar Lampung City has not implemented a wellplanned environmental plan for the safety of children from crime. The solving of child crimes in Bandar Lampung City is still reactive in tackling criminal cases, not preventive by organizing the residential, school, and other public spaces in a well planned and well managed by the municipal government by involving the surrounding community.